2019
DOI: 10.1039/c9cp04095a
|View full text |Cite
|
Sign up to set email alerts
|

Growth and stability of Pt nanoclusters from 1 to 50 atoms on h-BN/Rh(111)

Abstract: We investigated growth and temperature stability of Pt nanoclusters from 1 to 50 atoms on h-BN/Rh(111) using high-resolution XPS and STM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 39 publications
1
25
0
1
Order By: Relevance
“…The same group used another template h-BN/Ir (111) allowing stabilization of Ir clusters containing 6 to 175 atoms up to 700K under UHV [24]. On h-BN/Rh(111) another group has prepared at RT, under UHV, Pt single atoms and Ptn clusters (n=2-50) [25]. Pt clusters containing around 12 atoms were stable up to 400 K [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group used another template h-BN/Ir (111) allowing stabilization of Ir clusters containing 6 to 175 atoms up to 700K under UHV [24]. On h-BN/Rh(111) another group has prepared at RT, under UHV, Pt single atoms and Ptn clusters (n=2-50) [25]. Pt clusters containing around 12 atoms were stable up to 400 K [25].…”
Section: Introductionmentioning
confidence: 99%
“…On h-BN/Rh(111) another group has prepared at RT, under UHV, Pt single atoms and Ptn clusters (n=2-50) [25]. Pt clusters containing around 12 atoms were stable up to 400 K [25]. Another study with the same template has shown that Pd single atoms are mobile and coalesce at RT under UHV [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, if during the experiments, because of the temperature or the chemical environment, diffusion occurs, the initial wellcharacterized system disappears leadingand is replaced by a new and inoperable system. The experimental conditions can be sufficient to initiate the diffusion of monomers [8], dimers [13], but also larger clusters [9]. At present, the most common technique to determine the size statistics of very small clusters is to use an STM (Scanning Tunneling Microscope) which provides safely the ratio between occupied and unoccupied sites, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Deposited copper clusters rapidly and naturally coalesce into larger clusters [18] in a process known as Ostwald ripening, and it does not seem possible to study such small, size-selected clusters deposited on a support. This is a trend with many materials and obtaining small clusters is a challenge more often than not [254], exceptions being those cases in which the clusters can be trapped somehow [255,256], or when clusters are previously generated in vacuum where they can be size selected and then deposited on the target substrate [257,258].…”
Section: Motivationmentioning
confidence: 99%
“…This is of course also the case with most materials, and this effect is of theoretical and experimental interest in many fields such as the study of thin films [274][275][276][277] and epitaxial layer growth [278], of Moiré patterns on mismatched materials [279,280], 2D heterostructures [281][282][283], among many others. The effect of lattice mismatch is of more interest than just a technicality, since it can decide the electronic structure and stability of catalytic heterolayers [284,285], or form structures that can capture metallic clusters or other molecules, such as in graphene [255,286] which buckles under the induced mismatch strain, or hBN [256] which forms pores when deposited on certain metals. This mismatch has consequences for any interface between the two materials.…”
Section: Motivationmentioning
confidence: 99%